The terrestrial microsnail genus Aulacospira Möllendorff, 1890 (Eupulmonata, Stylommatophora, Hypselostomatidae) in Thailand with key to Thai species - Pongrat Dumrongrojwattana; Kitti Tanmuangpak (ZooKeys, 2020)
Thai terrestrial microsnails in the genus Aulacospira Möllendorff, 1890 are revised based on the collection of the Zoological Research Collection, Burapha University, Chonburi Province, Thailand and recently collected material. Three new species are described: Aulacospira nutadhirai sp.nov. from Southern Thailand, and Aulacospira tekavongae sp.nov. and Aulacospira vanwalleghemi sp. nov. from Eastern Thailand. The radula and genital system are described, and a key to Thai species is presented.